Lasers sensors very accurately measure both speed and length in real time. Issue 1 (14th January 2014) - Bloss, Richard
Abstract : Purpose: – Review of the advancements in non-contact laser sensors for much more accurate real time speed as well as length measurements. The paper aims to discuss these issues. Design/methodology/approach: – In-depth review of a number of applications of laser sensors. Findings: – A wide range of manufacturers in the converting industries have solved measurement problems and realized major improvements in product quality, cost of production and productivity by applying laser measurement as well as reduction in scrap. Practical implications: – Others with the need to make very accurate measurements of speed and length in real time may find that laser sensors may provide the answer. Originality/value: – An expert insight into how to solve real time speed and length measurement problems.